Adapting as I Go: An Analysis of the Relationship between Academic Expectations, Self-Efficacy, and Adaptation to Higher Education - Mafalda Campos; Francisco Peixoto; Rui Bártolo-Ribeiro; Leandro S. Almeida (MDPI AG, 2022)
Transition to higher education is increasingly becoming a common stage in young adulthood, which highlights the importance of studying what could contribute for a better adaptation to higher education. The aim of this study was to explore the relationship between academic expectations, self-efficacy, and adaptation to higher education during the first two years of college (i.e., the first two years of a higher education degree). Portuguese college students participated in a longitudinal data collection resorting to the Academic Expectations Questionnaire (T1 and T3), the Self-Efficacy in Higher Education Scale (T2 and T3), and the Questionnaire for Higher Education Adaptation (T2 and T3). Structural equation modeling analysis was conducted to test a model correlating academic expectations, self-efficacy, and adaptation, as well as a mediation model where a full mediation of self-efficacy was observed between the relationship between academic expectations and higher education expectations. This study delivers a unique longitudinal view on the experience of the first two years of college, showing a significant role of expectations and self-efficacy in order to achieve a better adaptation process. Results are useful for institutions to adapt the way they present themselves and manage students' expectations.